Chromosome-level genome assembly of the aphid Megoura crassicauda - Tianyu Huang; Xu Cheng; Bing Wang; Guirong Wang (Scientific Data)
Abstract Megoura crassicauda (Hemiptera: Aphididae) is a major pest species that inflicts significant damage on various legume crops worldwide, causing substantial global economic losses. In this study, we present a chromosome-scale genome assembly of M. crassicauda. By integrating PacBio long-read sequencing, Illumina short-read sequencing, and Hi-C scaffolding techniques, we constructed a genome assembly spanning 424.45 Mb genome. Approximately 93.74% of the assembly was successfully anchored into five scaffolds, with contig and scaffold N50 reaching 5.55 Mb and 103.55 Mb, respectively. The genome completeness, as evaluated by BUSCO, achieved a completeness score of 97.75%. Additionally, a total of 14,717 protein-coding genes were identified. This high-quality genome assembly of M. crassicauda serves as a valuable genomic resource, facilitating further studies into the ecological adaptations of M. crassicauda and the development of pest control strategies.